Brain mapping for long-term recovery of gait after supratentorial stroke: A retrospective cross-sectional study. Issue 16 (April 2018) - Kim, Dae Hyun; Kyeong, Sunghyon; Do, Kyung Hee; Lim, Seong Kyu; Cho, Hyong Keun; Jung, Suk; Kim, Hye Won
Abstract : Abstract: The recovery of independent gait after stroke is a main goal of patients and understanding the relationship between brain lesions and the recovery of gait can help physicians set viable rehabilitation plans. Our study investigated the association between variables of gait parameters and brain lesions. Fifty poststroke patients with a mean age of 67.5 ± 1.3 years and an average duration after onset of 62.2 ± 7.9 months were included. Three-dimensional gait analysis and magnetic resonance imaging were conducted for all patients. Twelve quantified gait parameters of temporal-spatial, kinematic, and kinetic data were used. To correlate gait parameters with specific brain lesions, we used a voxel-based lesion symptom mapping analysis. Statistical significance was set to an uncorrected P value <.005 and cluster size >10 voxels. Based on the location of a brain lesion, the following results were obtained: The posterior limb of the internal capsule was significantly associated with gait speed and increased knee extension in the stance phase. The hippocampus and frontal lobe were significantly associated with cadence. The proximal corona radiata was significantly associated with stride length and affected the hip maximal extension angle in the stance phase. The paracentral lobule was significantly associated with the affected knee maximal flexion angle in the swing phase and with the affected ankle maximal dorsiflexion angle in the stance phase. The frontal lobe, thalamus, and the lentiform nucleus were associated with kinetic gait parameters. Cortical, proximal white matter, and learning-related and motor-related areas are mainly associated with one's walking ability after stroke.